STUDI PENDAHULUAN DAERAH PROSPEK PANASBUMI BERDASARKAN DATA MANIFESTASI PANASBUMI, GEOKIMIA DAN ISOTOP FLUIDA PANASBUMI KOMPLEK GUNUNG TELOMOYO, KABUPATEN SEMARANG, JAWA TENGAH - Rizki Trisna Hutami; Yoga Aribowo; Dian Agus Widiarso (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
Telomoyo Mountain (area) is one of geothermal prospect area in Indonesia which is shown by many geothermal manifestations around the mountain. Telomoyo Mountain (area) is located in two regencies, Semarang and Magelang, Central Java. The purpose of this study is to get vision about geothermal model system in Telomoyo Mountain based on geothermal manifestation data, geothermal fluid geochemistry, and geothermal fluid isotope.Based on manifestation mapping there are two kinds of manifestation, warm spring and alteration. Warm springs are spread in Candi Dukuh and Candi Umbul with neutral pH characteristic and 36oC water temperature. Based on fluid geochemistry analysis the type of fluid is chloride-bicarbonate water, and based on Na-K-Mg comparison the fluid is immature water. Based on isotope 18O and 2H analysis, warm spring has mixed with meteoric water. Altered rocks are found in Desa Dangkel, Desa keningar, Desa Sepakung, and Desa Kendal Duwur with the type of alteration is argillic – advanced argillic. Based on petrography analysis, lithology in this area are andesitic lava, tuff breccia, and pyroclastic breccia. Based on XRD analysis, altered minerals in rock which is argillic type are smectite, halloysite, kaolinite, and jarosite. In rock which has advanced argilic type, there are dickite, phyrophillite, alunite, diaspora, cristobalite, and pyrite. Dickite and alunite mineral are typical mineral for physicochemical environment with acid in pH and 230 – 260 oC in temperature. Candi Umbul and Candi Dukuh warm spring shows the lateral outflow zone of the geothermal system, while advanced argillic alteration shows the upflow zone of geothermal system.